Trade, environment, and the WTO : a framework for moving forward - Sampson, Gary P. (Overseas Development Council WashingtonUS, 1999)
Proposes a new way of thinking about initiatives designed to reconcile trade and environmental goals - a framework for action. Focuses on five issues viz. transparency and public access; trade liberalization and the environment; product- and process-related environmental standards; multilateral environmental agreements and the WTO; and, environment-related disputes.